2008
DOI: 10.1159/000161578
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Kakkonto in a Mouse Model of Food Allergy with Gastrointestinal Symptoms

Abstract: Background: The number of patients with food allergy has increased dramatically over the last several decades. However, there is no effective drug for food allergies. In the present study, we evaluated the effects of kakkonto, a traditional Japanese herbal medicine, in a mouse model of food allergy with gastrointestinal symptoms. Methods: BALB/c mice were systemically sensitized twice with ovalbumin (OVA) and then were repeatedly given OVA by oral intubation (OVA mice). Kakkonto was administered orally before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 81 publications
(56 reference statements)
4
54
0
Order By: Relevance
“…Recently, it has been reported that intestinal mucosal immunity plays an important role in FA [1,6,7]. In our FA model, the enhancement of Th2-type immune responses in intestinal mucosal immunity is one of the most pivotal etiologies of FA [1], consistent with previous studies in another mouse FA model [6,7].…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Recently, it has been reported that intestinal mucosal immunity plays an important role in FA [1,6,7]. In our FA model, the enhancement of Th2-type immune responses in intestinal mucosal immunity is one of the most pivotal etiologies of FA [1], consistent with previous studies in another mouse FA model [6,7].…”
Section: Introductionsupporting
confidence: 90%
“…However, effective drug therapies for FA are not available. We have previously suggested that kakkonto is a potential therapeutic drug for FA, using our mouse FA model with gastrointestinal symptoms [1]. Kakkonto is a traditional Japanese herbal medicine that originated in China and is composed of the following 7 species of medicinal plants: Puerariae radix (23.5%), Cinnamomi cortex (18.8%), Zizyphi fructus (17.6%), Paeoniae radix (11.8%), Ephedrae herba (17.6%), Zingiberis rhizoma (5.9%) and Glycyrrhizae radix (11.8%).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, EJT treatment led to a decrease in plasma mMcpt1 levels in EJT-treated mice. mMcpt1 is one of the mast cell proteases found in mucosal mast cells, and previous studies showed that plasma mMcpt1 levels were significantly increased in mice with FA [9,30]. These findings raise the possibility that EJT might suppress plasma mMcpt1 levels without affecting mucosal mast cell numbers, thus controlling their function and suppressing degranulation.…”
Section: Discussionmentioning
confidence: 72%
“…We also found that the number of mucosal mast cells in the small intestine was higher in mice with FA than those in control mice. Both FAHF-2 [6] and kakkonto [9] were previously shown to reduce the number of mast cells in the intestines. Thus, we expected EJT-treated mice to be protected from infiltrating mast cells in the intestines; however, the number of mast cells in the intestines was not different between FA and EJT-treated mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation